Urgensi Regulasi Cyber Notary Dalam Mendukung Kepastian Hukum Di Era Digital - Abdillah, Satrio; Saputra, Hamanda Hadi (Lex Stricta : Jurnal Ilmu Hukum, 2025)
The urgency of this research lies in the urgent need to address the gap in Cyber notary regulations that have the potential to weaken legal certainty in the digital era. This research aims to identify challenges and formulate a regulatory concept that is adaptive to technological developments. Thus, it is expected to strengthen legal protection for parties in electronic transactions. The focus of this research is in line with the Sustainable Development Goals (SDGs), especially Goal 16: Peace, Justice, and Strong Institutions. This research supports the creation of responsive and transparent legal institutions by strengthening Cyber notary regulations in the digital era. This research method uses a qualitative approach analyzed using NVivo 12 Plus through transcription, data import, coding, and visualization. Data validity is maintained through source triangulation to ensure the reliability of the findings. This study's findings indicate that implementing Cyber notary regulations in the digital era is critical to guarantee legal validity, increase legal certainty and protection, and support safe digital transformation in notary services. Implementing cyber notaries in Indonesia still faces significant obstacles: the absence of specific regulations, limited technological infrastructure, lack of human resources, digital competence, and high data security and privacy risks. Therefore, regulatory development needs to prioritize six main aspects: validation of electronic deeds, standardization of procedures and technology, data protection and privacy, improving the digital competence of notaries, periodic supervision, and dispute resolution mechanisms.